Research on the impact of climate change on green and low-carbon development in agriculture - Jie Cai; Pan Zheng; Yiwei Xie; Zhimin Du; Xiaojing Li (Ecological Indicators)
The sustainable growth of agricultural production is substantially threatened by climate change, which has prompted a shift toward sustainable and environmentally friendly agricultural practices. This study utilizes provincial-level panel data from 2011 to 2020 to construct an indicator system for measuring the levels of Green and Low-Carbon Development in Agriculture (GLDA) in China. The temporal evolution and spatial distribution of climate change and GLDA are analyzed, with the impact mechanism of climate change on GLDA evaluated using both a benchmark regression model and a moderation effect model. The findings indicate that: 1) The aggregate level of GLDA in China has improved. Yet, there are disparities among regions. The central region has the highest GLDA level, while the eastern region is expanding at a rapid speed. Conversely, the western region is expanding at a slower pace. 2) The GLDA has been significantly inhibited by the impact of climate change, which is characterized by precipitation anomalies and accumulated temperature. The eastern region has not been significantly suppressed, while the central region has been significantly impacted by anomalous accumulated temperature and precipitation anomalies. The western region is primarily affected by abnormal precipitation.3) The inhibitory effect of accumulated temperature on GLDA in China has been alleviated by agricultural technological advancements; however, their influence on precipitation anomalies is restricted. The regulatory effect in the eastern region is negligible, while agricultural technological progress in the central and western regions has significantly alleviated the suppressive effect of abnormal precipitation on GLDA. However, the moderating effect on temperature anomalies is not immediately evident. Consequently, policy recommendations are proposed from a variety of perspectives to mitigate the effects of climate change and advance the green and GLDA. These recommendations include the formulation of incentive policies and regulations, as well as the support of agricultural construction.